Ignition delay time correlation of fuel blends based on Livengood-Wu description. (1st December 2017) - Khaled, Fethi; Badra, Jihad; Farooq, Aamir
Abstract: In this work, a universal methodology for ignition delay time (IDT) correlation of multicomponent fuel mixtures is reported. The method is applicable over wide ranges of temperatures, pressures, and equivalence ratios. n -Heptane, iso-octane, toluene, ethanol and their blends are investigated in this study because of their relevance to gasoline surrogate formulation. The proposed methodology combines benefits from the Livengood-Wu integral, the cool flame characteristics and the Arrhenius behavior of the high-temperature ignition delay time to suggest a simple and comprehensive formulation for correlating the ignition delay times of pure components and blends. The IDTs of fuel blends usually have complex dependences on temperature, pressure, equivalence ratio and composition of the blend. The Livengood-Wu integral is applied here to relate the NTC region and the cool flame phenomenon. The integral is further extended to obtain a relation between the IDTs of fuel blends and pure components. Ignition delay times calculated using the proposed methodology are in excellent agreement with those simulated using a detailed chemical kinetic model for n -heptane, iso-octane, toluene, ethanol and blends of these components. Finally, very good agreement is also observed for combustion phasing in homogeneous charge compression ignition (HCCI) predictions between simulations performed with detailed chemistry and calculations using the developed ignition delay correlation.